PERANCANGAN MEDIA PEMBELAJARAN MATERI BILANGAN BERBASIS MULTIMEDIA DENGAN METODE MIND MAPPING PADA SISWA KELAS VII SMPN 35 SEMARANG - Setiyo Prihatmoko; Sumaryanto Sumaryanto; Langga Jaya Herlansyah (STEKOM PRESS, 2022)
This research is motivated by the problem of lack of motivation and attention of students in following the teaching and learning process in the classroom because teaching and learning activities still use conventional methods. This makes students have difficulty in understanding the material being studied so that basic competencies and KKM are not achieved. This study uses the Research and Development (RnD) product development method, using 6 out of 10 research stages, namely potential and problems, data collection, product design, design validation, design improvement and product testing. In this study, researchers used multimedia with the Mind Map method as an interesting learning medium by using a computer that can display text, images, video, and audio so that the learning process is more enjoyable for students. The results of this study are multimedia-based learning media using the Mind Map method. The validity value of media experts is 3.6 which is declared feasible, while the validity value of material experts is 3.8 which is declared feasible, and increases students' understanding and interest as users from 61% initially to increase to 86.11%.